Graph Convolutional Network Based Fault Detection and Identification for Low-voltage DC Microgrid - Pandey, Ambuj; Mohanty, Soumya R. (State Grid Electric Power Research Institute Nanjing Branch, 2022)
This paper presents a novel fault detection and identification method for low-voltage direct current (DC) microgrid with meshed configuration. The proposed method is based on graph convolutional network (GCN), which utilizes the explicit spatial information and measurement data of the network topology to identify a fault. It has a more substantial feature extraction ability even in the presence of noise and bad data. The adjacency matrix for GCN is developed by considering the network topology as an inherent graph. The bus voltage and line current samples after faults are regarded as the node attributes. Moreover, the DC microgrid model is developed using PSCAD/EMTDC simulation, and fault simulation is carried out by considering different possible events that include environmental and physical conditions. The performance of the proposed method under different conditions is compared with those of different machine learning techniques such as convolutional neural network (CNN), support vector machine (SVM), and fully connected network (FCN). The results reveal that the proposed method is more effective than others at detecting and classifying faults. This method also possesses better robustness under the presence of noise and bad data.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: DC microgrid; fault detection; graph convolution network; topological information; Convolution; Fault detection; Network topology; Neural networks; Support vector machines